Respiratory virus of severe pneumonia in South Korea: Prevalence and clinical implications. - Hyung-Jun Kim; Sun Mi Choi; Jinwoo Lee; Young Sik Park; Chang-Hoon Lee; Jae-Joon Yim; Chul-Gyu Yoo; Young Whan Kim; Sung Koo Han; Sang-Min Lee (PLoS ONE)
Background Severe viral pneumonia is associated with a high mortality rate. However, due to the vulnerability of critically ill patients, invasive diagnostic methods should be performed with caution in the intensive care unit (ICU). It would be helpful if the prevalence, risk factors, and clinical impact of virus detection are elucidated. Methods We evaluated patients with severe pneumonia between January 1st 2008 and December 31st 2015. Reverse transcription-polymerase chain reaction (RT-PCR) analysis was performed for 8 respiratory viruses when viral pathogen could not be excluded as the origin of severe pneumonia. The baseline characteristics, laboratory results, microbiological findings, and clinical outcomes of the patients were analyzed. Results Of the 2,347 patients admitted to the medical ICU, 515 underwent RT-PCR for respiratory viruses, 69 of whom had positive results. The detection rate was higher during the winter, with a community onset, in patients with history of recent chemotherapy, and low platelet count. Additional bronchoscopic sampling along with upper respiratory specimen increased the yield of viral detection. Respiratory syncytial virus was the most common pathogen detected, while influenza A was the most common virus with bacterial coinfection. Respiratory virus detection led to changes in clinical management in one-third of the patients. Conclusions The detection of viral pathogens in patients with severe pneumonia is not rare, and can be more common in certain group of patients. Invasive sampling for RT-PCR can be helpful, and such detection can lead to positive changes in clinical management.